The harmfulness of white mold peas - Pikovskyi, M.; Kyryk, M.; Arnauta, N. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2018)
As a result revealed, dominance of white mold stem forms on pea plants has been revealed. The symptoms of the disease were characterized by changing signs: the formation of moisture-rich areas, the formation of a white cotton-like mycelium and sclerotia of the pathogen, bleaching and cracking of diseased stems. It was established that, depending on the degree of development of the disease, the amount of beans formed on the plants decreased from 0.9 pieces up to 9.0 pcs. In variants with the initial degree of development of the disease, no affected white rot was found. At the same time, with an increase in the intensity of the development of the disease on pea crops, the number of infected beans increased. The negative effect of white pea stem mold on seed yield was revealed. With the maximum development of the disease on pea stalks (grade 3), the mass of 1000 seeds decreases by 92 g. According to the research results, linear equations have been constructed that allow predicting the yield losses of peas affected by white mold.